State crisis theory: A systematization of institutional, socio-ecological, demographicstructural, world-systems, and revolutions research - Tilman Hartley (Post-growth Economics Network (PEN), 2023)
Today's ecological and political instability has stimulated interest in how similar problems have arisen in the past - and how they have been resolved. But this research has long been divided along different research traditions. I draw together five broad research strands: neo-institutionalism, socio- ecological systems, demographic-structural theories, world-systems approaches, and revolutions research. I begin by establishing that each of these five traditions proposes to explain state crisis, in the sense of a decisive turning point from which the state might not emerge in its current form. But each of the five strands proposes a slightly different set of central hypotheses, and draws on a slightly different set of cases in support. Systematizing these hypotheses, I draw attention to a neglected distinction between crises that take place in different ecological-economic conditions. This is because crises that occur in conditions of worsening scarcity are hypothesized to have very different causes and trajectories to crises that occur in conditions of sufficiency. But beyond this fundamental scarcity/sufficiency distinction, I find no other contradictions between different hypotheses. Systematizing these theories of state crisis thus establishes a framework for testing these competing, but compatible, hypotheses.
Keywords: 330; demographic-structural theory; institutions; revolutions; socio-ecological systems; state crisis; worldsystems analysis